2020
DOI: 10.1186/s12933-020-01038-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ABO blood groups and cardiovascular disease in type 1 diabetes according to diabetic nephropathy status

Abstract: Background: ABO blood groups have previously been associated with cardiovascular disease (CVD) in the general population. This study aimed to investigate the potential relationship between ABO blood groups and CVD in individuals with type 1 diabetes according to diabetic nephropathy (DN) status. Methods: Adults with type 1 diabetes (4531 individuals) from the FinnDiane Study were evaluated. DN was determined by two out of three measurements of urinary albumin excretion rate. Albuminuria was defined as an excre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Parente et al 49 found using multivariate analysis that blood group A was a risk factor for ischemic heart disease in individuals with type 1 DM and microalbuminuria but not in those with macroalbuminuria or end-stage renal disease. A case-control study on women with type 2 DM who were similar in other cardiovascular risk factors demonstrated that blood group AB could be considered a risk factor for developing CAD in these patients.…”
Section: Cardiovascular Diseases In Patients With Comorbiditiesmentioning
confidence: 99%
“…Parente et al 49 found using multivariate analysis that blood group A was a risk factor for ischemic heart disease in individuals with type 1 DM and microalbuminuria but not in those with macroalbuminuria or end-stage renal disease. A case-control study on women with type 2 DM who were similar in other cardiovascular risk factors demonstrated that blood group AB could be considered a risk factor for developing CAD in these patients.…”
Section: Cardiovascular Diseases In Patients With Comorbiditiesmentioning
confidence: 99%
“…Levels of high sensitivity C-reactive protein and the number of antibiotic purchases per year were significantly higher in the type A group. This suggests some sort of inflammatory/infectious mediator which links the type A blood association to certain outcomes [21] . Additionally, in a study by Oner et al, Type A blood was the most dominant genotype in all diabetic groups in both genders, while type AB was significantly more frequent among T1DM [22] .…”
Section: Ii-increased Manifestations Of Covid-19 In Non-o Individualsmentioning
confidence: 99%
“…Although there are conflicting results, the relationship between atherothrombosis and non-O group has been shown in many studies. 11–14 Most of the above mentioned studies focused on coronary artery disease. However, it is well known that coronary artery disease and PAD share similar risk factors and pathogenetic process.…”
Section: Discussionmentioning
confidence: 99%